Porous array flexible electronic skin based on sacrificial template method and preparation method thereof
Patent Information
- Application Number
- CN202611071848.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对现有柔性电子皮肤在工业氟塑膜微小缺陷检测中存在的灵敏度不足、结构不可控、制备工艺复杂且难以规模化生产的问题,本发明提供一种基于牺牲模板法的多孔阵列式柔性电子皮肤及其制备方法,通过CCTO纳米纤维高介电填料与可控多孔阵列结构的协同效应,实现器件灵敏度的大幅提升,同时具备工艺简单、结构可控、共形贴合能力强的优势
高介电填料与多孔结构协同提升传感灵敏度。本发明采用一维CCTO纳米纤维替代传统零维颗粒作为高介电填料,利用一维结构的空间位阻效应抑制填料团聚,提升分散均匀性的同时降低对基体柔性的劣化作用,有效提高复合介电层的相对介电常数;同时通过3D打印牺牲模板在介电层内部构建可控的阵列式通孔结构,大幅降低材料的等效杨氏模量,使器件在微小压力作用下即可产生显著的法向形变,减小极板间距。二者协同作用下,器件在低压力区间的灵敏度较实心结构提升一个数量级以上,可精准捕捉氟塑膜表面0.1mm级的微小凸起缺陷。
Smart Images

Figure CN122961590A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of flexible electronic skin and flexible sensing technology, specifically to porous array flexible electronic skin based on the sacrificial template method and its preparation method. Background Technology
[0002] With the rapid advancement of intelligent manufacturing and industrial technology, surface quality control of industrial products has become a core element in ensuring product performance and improving production yield. Industrial fluoroplastic films, as a special engineering film with excellent corrosion resistance, high-temperature resistance, and insulation properties, are widely used in high-end fields such as aerospace cable coating, electronic and electrical substrate lining, chemical anti-corrosion lining, and new energy battery separators. During the continuous extrusion production of fluoroplastic films, factors such as fluctuations in raw material purity, unstable extrusion process parameters, and dust and impurities in the production environment can easily cause micron- to sub-millimeter-level black spots, white spots, crystal points, and protrusions on their surface. These defects are small in size but significantly harmful, directly disrupting the structural continuity of the fluoroplastic film, greatly reducing its mechanical strength, breakdown voltage, and corrosion resistance life, and in severe cases, even causing safety accidents such as equipment leakage and short circuits.
[0003] Currently, the industry mainly relies on machine vision systems for online inspection of surface defects in fluoroplastic films. These systems use high-speed cameras to capture images of the film surface and combine them with algorithms to identify defects. However, this technology has significant limitations in practical applications: for tiny white spots, low-contrast transparent protrusions, and subsurface defects under transparent substrates, traditional optical imaging methods lack depth sensing capabilities, resulting in a false negative rate of over 15%. Furthermore, they cannot quantify the three-dimensional morphological parameters of defects, such as height and hardness, making it difficult to meet the quality control requirements of high-end fluoroplastic films.
[0004] Flexible electronic skin, a novel electronic device that mimics the tactile sensing function of human skin, offers a new technological approach for detecting micro-defects on complex surfaces due to its excellent flexibility, conformal fit, and high sensitivity. Capacitive flexible electronic skin, based on the parallel-plate capacitive sensing principle, detects pressure by sensing the capacitance change caused by the deformation of the dielectric layer under pressure. It boasts advantages such as fast response, low power consumption, and good stability, making it the preferred technology for industrial inspection scenarios. Existing capacitive electronic skins mostly use polydimethylsiloxane (PDMS) as the elastic matrix. To improve sensing sensitivity, researchers often dope PDMS with high-dielectric-constant ceramic fillers such as titanium dioxide, barium titanate, and calcium copper titanate (CCTO). CCTO, with its giant dielectric constant, is an ideal filler for improving the dielectric properties of composite materials. However, existing solutions often use zero-dimensional CCTO nanoparticles as fillers. Due to the high surface energy and intense Brownian motion of nanoparticles, they are prone to agglomeration, which not only causes uneven dielectric properties but also significantly increases the modulus of the composite material, degrading the flexibility and conformal fit of the electronic skin.
[0005] To further enhance sensitivity, high-performance electronic skins typically incorporate microstructures such as micropyramids, micropillars, and porous structures within the dielectric layer to reduce the effective elastic modulus and increase compressive deformation. However, existing microstructure fabrication processes have significant limitations: micro / nano fabrication equipment such as photolithography and dry etching are expensive and cumbersome, making large-area fabrication difficult; sacrificial particle methods using salt templates and sugar templates result in random pore distribution, uncontrollable size, and poor batch consistency; direct 3D printing of high-fill-volume ceramic / polymer composite slurries is limited by the slurry's rheological properties, making it difficult to simultaneously guarantee printing accuracy and material dielectric properties. Furthermore, existing sacrificial template methods mostly employ planar spin-coating processes to fabricate thin films, forming only shallow pore structures on the material surface. This makes it difficult to construct a pervasive, three-dimensional, controllable array of pore structures in thick-film devices, limiting the deformation capability and sensitivity improvement of electronic skins under normal stress, and failing to meet the high-precision detection requirements of minute defects in industrial fluoroplastic films. Therefore, developing a flexible electronic skin with simple processes, controllable structure, high sensitivity, and ease of large-scale fabrication is a pressing technical problem in the field of industrial surface inspection. Summary of the Invention
[0006] To address the problems of insufficient sensitivity, uncontrollable structure, complex fabrication process, and difficulty in large-scale production of existing flexible electronic skins for detecting minute defects in industrial fluoroplastic films, this invention provides a porous array flexible electronic skin based on the sacrificial template method and its fabrication method. Through the synergistic effect of CCTO nanofiber high dielectric filler and controllable porous array structure, the device sensitivity is significantly improved, while also possessing the advantages of simple process, controllable structure, and strong conformal bonding capability.
[0007] The technical solution adopted by this invention to solve its technical problem is: a method for preparing porous array flexible electronic skin based on the sacrificial template method, comprising the following steps: Step 1: Calcium nitrate, copper acetate, and tetrabutyl titanate are mixed in a molar ratio of 1:3:4. Polyvinylpyrrolidone is added and dissolved in a mixed solution of acetic acid and ethanol. After stirring for 6 hours, a blue transparent solution is formed. Light blue precursor nanofibers are obtained by electrospinning. The nanofibers are collected and placed in a tube furnace for heat treatment to obtain CCTO nanofibers. Step 2: Prepare a PLA mold with an inner groove size of 100mm×10mm×1mm by 3D printing, and then prepare a PVA sacrificial layer film by 3D printing. Mix PDMS, curing agent and CCTO nanofibers thoroughly to obtain a composite slurry and pour it into the mold. Place a PVA sacrificial layer film of appropriate size into the mold, remove air bubbles and cure and dry at 50℃ to obtain a composite elastomer film. Step 3: Remove the composite elastomer membrane and place it in deionized water. After removing the PVA sacrificial layer film, attach a nickel cloth conductive layer to the upper and lower surfaces of the composite elastomer membrane and lead out wires. Then, encapsulate and protect it with a polyimide film to obtain a porous array flexible electronic skin based on the sacrificial template method.
[0008] Specifically, in step 1, the temperature of the tubular furnace heat treatment is 850℃, the holding time is 2h, the heating rate is 2℃ / min, and the heat treatment atmosphere is air.
[0009] Specifically, in step 1, the molecular weight of polyvinylpyrrolidone is 1.3 million, and the amount added is 8% of the total mass of the precursor solution; the volume ratio of acetic acid to ethanol is 1:3; the process parameters of electrospinning are: spinning voltage 18kV, receiving distance 15cm, injection speed 0.8mL / h, needle specification 21G, ambient temperature 25℃, and relative humidity 40%.
[0010] Specifically, in step 2, the PVA sacrificial layer film is prepared using a sparse printing process with a fill rate of 50%, meaning that the ratio of the area covered by the printed lines to the total area of the film is 50%, the number of printed layers is 50% of the number of full-layer printed layers, and the filling pattern is a square grid array.
[0011] Specifically, in step 2, the mass ratio of PDMS to curing agent is 10:1, and the mass ratio of PDMS to CCTO nanofibers is 50:1. The mixing process of the composite slurry is as follows: first, PDMS and curing agent are magnetically stirred for 30 minutes, CCTO nanofibers are added and magnetic stirring is continued for 1 hour, then ultrasonically dispersed for 30 minutes, and then vacuum degassing is performed for 10 minutes.
[0012] Specifically, before attaching the nickel cloth conductive layer in step 3, the upper and lower surfaces of the composite elastomer film need to be treated with oxygen plasma in advance. The treatment power is 100W, the treatment time is 60s, and the vacuum degree is 10Pa.
[0013] Specifically, in step 3, the polyimide film has a thickness of 0.1 mm and a width of 12 mm. During encapsulation, the polyimide film completely covers the nickel cloth conductive layer and extends 1 mm beyond the edge of the composite elastomer film. Sealing is achieved by hot pressing.
[0014] The porous array flexible electronic skin based on the sacrificial template method is prepared by the above-mentioned preparation method. The electronic skin includes an upper polyimide encapsulation layer, an upper nickel cloth conductive layer, a porous array CCTO / PDMS composite dielectric layer, a lower nickel cloth conductive layer, and a lower polyimide encapsulation layer stacked from top to bottom. The porous array CCTO / PDMS composite dielectric layer has a regularly distributed array of through-hole structures inside.
[0015] The beneficial effects of this invention are: High-dielectric filler and porous structure synergistically enhance sensing sensitivity. This invention uses one-dimensional CCTO nanofibers instead of traditional zero-dimensional particles as the high-dielectric filler. The steric hindrance effect of the one-dimensional structure suppresses filler agglomeration, improving dispersion uniformity while reducing the deterioration on the substrate flexibility, effectively increasing the relative permittivity of the composite dielectric layer. Simultaneously, a controllable array of through-hole structures is constructed within the dielectric layer using a 3D-printed sacrificial template, significantly reducing the material's equivalent Young's modulus. This allows the device to produce significant normal deformation under minimal pressure, reducing the electrode spacing. The synergistic effect of these two factors improves the device's sensitivity in the low-pressure range by more than an order of magnitude compared to a solid structure, enabling precise detection of minute protrusions on the fluoroplastic film surface at the 0.1mm level.
[0016] The structure is precise and controllable, with good batch consistency. This invention uses 3D printing technology to prepare PVA sacrificial templates. The porosity, pore size and pore distribution can be precisely controlled by adjusting parameters such as printing infill rate, number of printing layers and infill pattern, overcoming the defects of random and uncontrollable pores in traditional salt templates and sugar templates. At the same time, the template preparation and device forming process have good repeatability, and the performance deviation between batches can be controlled within 5%, which is suitable for industrial mass production needs.
[0017] The fabrication process is simple and inexpensive. This invention eliminates the need for expensive micro-nano processing equipment such as photolithography and dry etching, and can be fabricated using only conventional processes such as electrospinning, 3D printing, and solution casting. The PVA sacrificial template can be completely removed by soaking in deionized water, eliminating the need for toxic chemical etchants. The process is short, easy to operate, and uses inexpensive raw materials, making it easy to achieve large-area, large-scale production.
[0018] With strong conformal bonding capability, it is suitable for complex curved surface inspection. Thanks to the high elasticity of the PDMS matrix and the low modulus of its porous structure, the electronic skin has excellent mechanical compliance and can be tightly attached to non-planar inspection surfaces such as rollers and curved workpieces to achieve seamless conformal contact. This eliminates the contact blind zone and signal fluctuation problems of hard sensors in curved surface inspection, making it suitable for online inspection scenarios of roller surfaces in industrial production lines.
[0019] The structure is stable and the service life is long. This invention introduces an oxygen plasma surface treatment process before electrode adhesion, which introduces polar groups by etching and activating the PDMS surface, significantly improving the interfacial bonding force between the nickel cloth electrode and the elastic substrate, avoiding problems such as electrode detachment and contact resistance drift during long-term cyclic bending; combined with the sealed encapsulation of PI film, it effectively isolates the device from external moisture and dust corrosion, improving the long-term stability and service life of the device in complex industrial environments. Attached Figure Description
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0021] Figure 1 A flowchart illustrating the fabrication method of a porous array flexible electronic skin based on the sacrificial template method provided in this embodiment of the invention; Figure 2 This is a schematic diagram of the layered structure of the flexible electronic skin prepared in Embodiment 1 of the present invention; Figure 3 This is an optical microscope image of the PVA sacrificial layer film prepared in Example 1 of the present invention, wherein... Figure 3 'a' represents the overall mesh structure at low magnification. Figure 3 b represents the line morphology under high magnification; Figure 4 This is an optical image of a porous array CCTO / PDMS composite elastomer film prepared according to Embodiment 1 of the present invention, wherein... Figure 4 a is a macroscopic physical image. Figure 4 b is a local pore morphology diagram; Figure 5 The capacitance response curves of the electronic skin obtained in Embodiment 1 of the present invention under different loads are shown below. Figure 5 'a' represents the response in the low-load range. Figure 5 b represents the response over the entire load range; Figure 6 This is a dynamic response characteristic diagram of the electronic skin obtained in Embodiment 1 of the present invention, wherein... Figure 6 'a' represents the response time versus recovery time curve. Figure 6 b represents the stability curve for 100 load-unload cycles; Figure 7 This diagram illustrates the application and detection results of the electronic skin fabricated according to the present invention in the detection of surface defects in industrial fluoroplastic films. Figure 7 a is a schematic diagram of the detection device. Figure 7 b is a schematic diagram of the defect detection principle. Figure 7 c represents the capacitance response curves for defects with different heights. Detailed Implementation
[0022] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.
[0023] like Figures 1-7 As shown, the method for fabricating porous array flexible electronic skin based on the sacrificial template method of the present invention includes the following steps: Step 1, Preparation of CCTO nanofibers: Calcium nitrate, copper acetate, and tetrabutyl titanate were weighed and mixed in a molar ratio of 1:3:4. A mixed solvent of acetic acid and ethanol was added, and the mixture was stirred until the solutes were completely dissolved. Polyvinylpyrrolidone (PVP) was added as a spinning aid, and the mixture was stirred continuously for 6 hours until a uniform and stable blue transparent precursor solution was formed. The precursor solution was injected into an electrospinning syringe, and electrospinning was performed by setting the spinning process parameters. The light blue precursor nanofibers on the aluminum foil were collected. The precursor nanofibers were placed in an alumina crucible and subjected to high-temperature calcination heat treatment in a tube furnace. After cooling in the furnace, calcium copper titanate (CCTO) nanofibers were obtained.
[0024] Further, in step 1, the volume ratio of acetic acid to ethanol is 1:3; the molecular weight of PVP is 1.3 million, and the amount added is 8% of the total mass of the precursor solution; the electrospinning process parameters are: spinning voltage 18kV, receiving distance 15cm, injection speed 0.8mL / h, needle specification 21G, ambient temperature controlled at 25℃, and relative humidity controlled at 40%; the calcination process parameters are: heating to 850℃ at a heating rate of 2℃ / min, holding at that temperature for 2h, and the entire process is carried out in an air atmosphere.
[0025] Step 2, Sacrificial Template Preparation and Composite Slurry Curing: A PLA mold was prepared using a fused deposition modeling (FDM) 3D printer, with an inner groove size of 100mm × 10mm × 1mm. A PVA sacrificial layer film was prepared using PVA filament as raw material using the same model 3D printer. The printing process adopted a sparse filling mode, and the porosity and pore size of the porous structure were controlled by adjusting the fill rate and the number of printed layers. The PDMS matrix and curing agent were mixed in proportion, stirred evenly, and then CCTO nanofibers were added. After thorough dispersion and degassing, a CCTO / PDMS composite slurry was obtained. The composite slurry was slowly injected into the PLA mold, and then the PVA sacrificial layer film was horizontally placed into the slurry in the mold, ensuring that the film was centered and completely immersed. After vacuum degassing to remove air bubbles from the slurry, the mold was placed in an oven for heating and curing to obtain a composite elastomer film.
[0026] Further, in step 2, the PVA sacrificial layer film has a fill rate of 50% (the ratio of the area covered by the printed lines to the total area of the film), the number of printed layers is 50% of the full-layer printing layer, the filling pattern is a square grid array, and the film size is 98mm×8mm×0.1mm; the mass ratio of PDMS to curing agent is 10:1, and the mass ratio of PDMS to CCTO nanofibers is 50:1; the preparation process of the composite slurry is as follows: first, PDMS and curing agent are magnetically stirred at room temperature for 30min, CCTO nanofibers are added and magnetic stirring is continued for 1h, then placed in an ultrasonic cleaner and ultrasonically dispersed at 200W power for 30min, and finally degassed under a vacuum of -0.09MPa for 10min; the curing and drying conditions are constant temperature curing at 50℃ for 4h.
[0027] Step 3, Post-processing and Device Encapsulation: The cured composite elastomer film is removed from the PLA mold and completely immersed in deionized water at 60°C. The internal PVA sacrificial layer film is removed by dissolving and eluting. The deionized water is changed every 6 hours during the immersion process, and short-term ultrasonication is used to promote PVA dissolution. After the PVA is completely removed, the composite elastomer film is removed and dried in a 60°C oven for 2 hours. The upper and lower surfaces of the composite elastomer film are treated with oxygen plasma to improve surface energy and wettability. Then, a nickel cloth conductive layer is smoothly adhered to the upper and lower surfaces and copper wires are led out. Finally, polyimide (PI) film is used to thermo-press encapsulate the upper and lower surfaces of the device to complete the fabrication of the porous array flexible electronic skin.
[0028] Furthermore, in step 3, the total soaking time for PVA dissolution is 24 hours, and the auxiliary ultrasonic time is 10 minutes each time; the plasma surface treatment parameters are: oxygen atmosphere, power 100W, treatment time 60s, vacuum degree 10Pa; the nickel cloth is 200 mesh nickel woven cloth with a thickness of 0.05mm, and conductive silver paste is used to achieve adhesion with the elastomer; the PI film has a thickness of 0.1mm and a width of 12mm. During encapsulation, the PI film completely covers the nickel cloth area and extends 1mm beyond the edge of the elastomer. The hot-press encapsulation parameters are: temperature 80℃, pressure 0.1MPa, and holding time 5min.
[0029] This invention provides a porous array flexible electronic skin prepared by the above-described method. The electronic skin has a five-layer stacked structure, consisting of an upper PI encapsulation layer, an upper nickel cloth electrode layer, a porous array CCTO / PDMS composite dielectric layer, a lower nickel cloth electrode layer, and a lower PI encapsulation layer from top to bottom. The composite dielectric layer has a regularly distributed array of through-holes with uniform pore distribution and consistent size, and an overall thickness of 1 mm.
[0030] The capacitive sensing mechanism of this invention is based on the fundamental formula of a parallel-plate capacitor: ; Where C is the capacitance value of the device, and the unit is farad; It is the vacuum permittivity, a fixed physical constant; denoted as the relative permittivity of the dielectric layer material, dimensionless; S is the area of the upper and lower electrodes facing each other, in square meters; d is the distance between the upper and lower electrodes, i.e., the thickness of the dielectric layer, in meters.
[0031] When the electronic skin is subjected to external pressure, the dielectric layer undergoes elastic deformation, leading to a decrease in the electrode spacing d and an increase in capacitance. This invention addresses this by using CCTO nanofibers doped with high dielectric constants to enhance the relative dielectric constant of the dielectric layer. On the one hand, the initial capacitance and the capacitance change per unit deformation are increased; on the other hand, the equivalent modulus of the dielectric layer is reduced by the porous array structure, so that the deformation under the same pressure is larger and the reduction of d is more significant. The two work together to improve the pressure sensitivity of the device.
[0032] Example 1: This example is the optimal parameter example. The specific steps for preparing the porous array flexible electronic skin are as follows: Step 1, Preparation of CCTO nanofibers. Following a stoichiometric ratio of calcium nitrate, copper acetate, and tetrabutyl titanate of 1:3:4, weigh 0.01 mol of calcium nitrate tetrahydrate, 0.03 mol of copper acetate monohydrate, and 0.04 mol of tetrabutyl titanate, and add them sequentially to a dry conical flask. Add 40 mL of a mixture of glacial acetic acid and anhydrous ethanol (volume ratio 1:3) to the conical flask, and stir at 300 rpm for 30 min on a magnetic stirrer until the solutes are completely dissolved, forming a homogeneous blue-green solution. Add 3.2 g of PVP powder with a molecular weight of 1.3 million to the solution, and continue stirring at 400 rpm for 6 h to obtain a transparent and homogeneous blue electrospinning precursor solution, in which PVP accounts for 8% of the total mass of the precursor solution. The precursor solution was loaded into a 5mL medical syringe, fitted with a 21G stainless steel needle, and placed on the injection pump of the electrospinning equipment. The spinning parameters were set as follows: injection speed 0.8mL / h, spinning voltage 18kV, vertical distance between the roller receiver and the needle 15cm, and roller speed 100r / min. The spinning environment temperature was controlled at 25℃ and the relative humidity at 40%. The high-voltage power supply was turned on for electrospinning, and the spinning time was 2h. A light blue precursor nanofiber membrane was collected on the aluminum foil-wrapped roller. The collected precursor nanofibers were removed from the aluminum foil, laid flat in an alumina crucible, and placed in a tube furnace for calcination. The calcination program was set as follows: the temperature was increased from room temperature to 850℃ at a rate of 2℃ / min, and held at 850℃ for 2 hours with dry air throughout the process. After the holding period, the furnace was allowed to cool naturally to room temperature. The resulting brown CCTO nanofibers were then obtained. X-ray diffraction characterization confirmed that they were pure-phase perovskite structure calcium copper titanate, with fiber diameters ranging from 200 to 300 nm.
[0033] Step 2, Sacrificial template preparation and composite slurry curing. A fused deposition modeling 3D printer was used to print the mold using PLA filament. The mold's outer dimensions were 120mm × 20mm × 2mm, and the internal groove dimensions were 100mm × 10mm × 1mm. The printing layer height was 0.1mm, and the wall thickness was 1.2mm. After printing, the inner groove of the mold was polished to ensure that the inner wall was smooth and burr-free. Using the same 3D printer, a sacrificial layer film was printed using PVA filament with an 88% degree of hydrolysis and model 1788. The printing parameters were set as follows: nozzle diameter 0.4 mm, layer height 0.02 mm, line width 0.4 mm, printing speed 40 mm / s, infill pattern of square grid, infill rate set to 50% (i.e., the ratio of the area covered by the printed lines to the total area of the film is 50%), and the number of printing layers set to 5, corresponding to 50% of the thickness of a full 10-layer print. A PVA grid sacrificial layer film with dimensions of 98 mm × 8 mm × 0.1 mm was obtained. Observation under an optical microscope showed that the grid lines were uniform and the pore distribution was regular. Weigh 10g of PDMS matrix (Dow Corning Sylgard 184) and 1g of matching curing agent, place them in a plastic beaker, and magnetically stir at 300r / min for 30min to ensure uniform mixing. Add 0.22g of CCTO nanofibers (PDMS to CCTO mass ratio of 50:1) and continue magnetic stirring for 1h to initially disperse the fibers in the PDMS. Then place the beaker in an ultrasonic cleaner, set the ultrasonic power to 200W, and ultrasonically disperse for 30min under ice-water bath conditions to further break up fiber agglomeration and form a uniform composite slurry. Place the composite slurry in a vacuum drying oven and degas for 10min under a vacuum of -0.09MPa to remove air bubbles introduced during stirring and ultrasonication. Slowly inject the degassed composite slurry into the inner groove of the PLA mold until the slurry surface is flush with the mold groove opening; use tweezers to pick up the PVA sacrificial layer film and slowly place it horizontally into the slurry, adjusting its position so that the film is in the center of the mold and completely immersed in the slurry, with equal distance from the upper and lower surfaces; place the mold in a vacuum drying oven again for 5 minutes to degauge and remove any remaining tiny air bubbles under the film; finally, place the mold in a 50°C electric constant temperature oven and cure at a constant temperature for 4 hours to obtain a fully cross-linked CCTO / PDMS composite elastomer film.
[0034] Step 3, Post-processing and Device Packaging. Remove the mold from the oven and allow it to cool to room temperature. Use tweezers to completely peel off the composite elastomer film along the mold edge. Immerse the elastomer film completely in a beaker containing 60°C deionized water to dissolve and remove the PVA sacrificial layer. Change the deionized water every 6 hours during immersion. Each time the water is changed, place the beaker in an ultrasonic cleaner and sonicate for 10 minutes to accelerate the dissolution and removal of PVA. After a total immersion time of 24 hours, remove the elastomer film and confirm a PVA removal rate of over 99% by weighing. Dry the eluted elastomer film in a 60°C oven for 2 hours to completely remove any residual moisture. Place the dried elastomer film in a plasma cleaner chamber, evacuate to 10 Pa, introduce oxygen, and set the plasma power to 100W. Treat the upper and lower surfaces of the elastomer for 60 seconds each to complete surface activation. Two pieces of 200-mesh nickel cloth, each 98mm x 8mm, were cut. A thin layer of conductive silver paste was evenly coated on the upper and lower surfaces of the activated elastomer. The conductive layer of nickel cloth was then smoothly attached, and air bubbles were gently pressed to remove them. The mixture was allowed to stand at room temperature for 2 hours to allow the silver paste to cure. A 0.1mm diameter copper wire was soldered to the edge of the nickel cloth as a signal lead. Two PI films, 0.1mm thick and 12mm wide, were cut and placed on the upper and lower nickel cloth surfaces, ensuring that the PI film completely covered the nickel cloth area and extended 1mm beyond the edge of the elastomer. The device was placed in a hot press, with the hot pressing temperature set to 80℃ and the pressure to 0.1MPa, and held for 5 minutes to ensure a tight bond between the PI film and the elastomer, achieving edge sealing. Finally, a porous array flexible electronic skin based on the sacrificial template method was obtained, with a total device thickness of approximately 1.3mm.
[0035] The electronic skin prepared in this embodiment was subjected to performance testing: a gradient pressure load was applied using a precision electronic universal testing machine, and capacitance signals were collected using a precision LCR meter. The test frequency was set to 1kHz, and the test voltage was 1V. The test results showed that the device can stably sense pressure loads ranging from 1g to 200g, and the sensitivity in the low pressure range (0~10kPa) can reach 1.25kPa. -1 Compared to a solid structure of the same thickness, the capacitance is improved by 8.7 times. In dynamic response testing, the device has a response time of 0.6s and a recovery time of 1s, demonstrating rapid pressure response capability. After 100 consecutive load-unload cycles, the capacitance response amplitude decay rate is less than 2%, exhibiting excellent cycle stability. When applied to the detection of protrusion defects on fluoroplastic film surfaces, the device can clearly identify all defects within a height range of 0.1mm to 1mm. The capacitance change shows a good linear relationship with the defect height, with a linear fit R0. 2 It reached 0.987.
[0036] Example 2: This example illustrates the fabrication of a porous array-type flexible electronic skin with low porosity parameters. The porosity of the dielectric layer is controlled by reducing the fill rate of the PVA sacrificial layer to balance the device's sensitivity and mechanical strength. The specific fabrication steps are as follows: Step 1, Preparation of CCTO nanofibers. Following a stoichiometric ratio of calcium nitrate, copper acetate, and tetrabutyl titanate of 1:3:4, weigh 0.01 mol of calcium nitrate tetrahydrate, 0.03 mol of copper acetate monohydrate, and 0.04 mol of tetrabutyl titanate, and add them sequentially to a dry conical flask. Add 40 mL of a mixture of glacial acetic acid and anhydrous ethanol (volume ratio 1:3) to the conical flask, and stir at 300 rpm for 30 min on a magnetic stirrer until the solutes are completely dissolved, forming a homogeneous blue-green solution. Add 3.2 g of PVP powder with a molecular weight of 1.3 million to the solution, and continue stirring at 400 rpm for 6 h to obtain a transparent and homogeneous blue electrospinning precursor solution, in which PVP accounts for 8% of the total mass of the precursor solution. The precursor solution was loaded into a 5mL medical syringe, fitted with a 21G stainless steel needle, and placed on the injection pump of an electrospinning device. Spinning parameters were set as follows: injection rate 0.8mL / h, spinning voltage 18kV, vertical distance between the roller receiver and the needle 15cm, and roller speed 100r / min. The spinning environment temperature was controlled at 25℃ and relative humidity at 40%. Electrospinning was performed with a high-voltage power supply for 2 hours, and a pale blue precursor nanofiber membrane was collected on a roller wrapped in aluminum foil. The collected precursor nanofibers were removed from the aluminum foil, spread evenly in an alumina crucible, and placed in a tubular resistance furnace for calcination. The calcination program was set as follows: heating from room temperature to 850℃ at a rate of 2℃ / min, holding at 850℃ for 2 hours with dry air circulated throughout. After holding, the furnace was allowed to cool naturally to room temperature, yielding brownish-red pure-phase CCTO nanofibers.
[0037] Step 2, Sacrificial template preparation and composite slurry curing. A fused deposition modeling 3D printer was used to print the mold using PLA filament. The mold's outer dimensions were 120mm × 20mm × 2mm, and the internal groove dimensions were 100mm × 10mm × 1mm. The printing layer height was 0.1mm, and the wall thickness was 1.2mm. After printing, the inner groove of the mold was polished to ensure that the inner wall was smooth and burr-free. Using the same 3D printer, a sacrificial layer film was printed using PVA filament with a hydrolysis degree of 88% and model 1788. The printing parameters were set as follows: nozzle diameter 0.4 mm, layer height 0.02 mm, line width 0.4 mm, printing speed 40 mm / s, infill pattern of square grid, infill rate of 40% (i.e., the ratio of the area covered by the printed lines to the total area of the film is 40%), and the number of printing layers was set to 5, corresponding to 50% of the full-layer printing thickness of 10 layers. A PVA grid sacrificial layer film with dimensions of 98 mm × 8 mm × 0.1 mm was obtained. Observation under an optical microscope showed that the grid spacing was larger than that in Example 1, the pore distribution was more regular, and the overall porosity was lower than that in Example 1. Weigh 10g of PDMS matrix (Dow Corning Sylgard 184) and 1g of matching curing agent, place them in a plastic beaker, and magnetically stir at 300r / min for 30min to ensure uniform mixing. Add 0.22g of CCTO nanofibers (PDMS to CCTO mass ratio of 50:1) and continue magnetic stirring for 1h to initially disperse the fibers in the PDMS. Then place the beaker in an ultrasonic cleaner, set the ultrasonic power to 200W, and ultrasonically disperse for 30min under ice-water bath conditions to further break up fiber agglomeration and form a uniform composite slurry. Place the composite slurry in a vacuum drying oven and degas for 10min under a vacuum of -0.09MPa to remove air bubbles introduced during stirring and ultrasonication. Slowly inject the degassed composite slurry into the inner groove of the PLA mold until the slurry surface is flush with the mold groove opening; use tweezers to pick up the PVA sacrificial layer film and slowly place it horizontally into the slurry, adjusting its position so that the film is in the center of the mold and completely immersed in the slurry, with equal distance from the upper and lower surfaces; place the mold in a vacuum drying oven again for 5 minutes to degauge and remove any remaining tiny air bubbles under the film; finally, place the mold in a 50°C electric constant temperature oven and cure at a constant temperature for 4 hours to obtain a fully cross-linked CCTO / PDMS composite elastomer film.
[0038] Step 3, Post-processing and Device Packaging. Remove the mold from the oven and allow it to cool to room temperature. Use tweezers to completely peel off the composite elastomer film along the mold edge. Immerse the elastomer film completely in a beaker containing 60°C deionized water to dissolve and remove the PVA sacrificial layer. Change the deionized water every 6 hours during immersion. Each time the water is changed, place the beaker in an ultrasonic cleaner and sonicate for 10 minutes to accelerate the dissolution and removal of PVA. After a total immersion time of 24 hours, remove the elastomer film and confirm a PVA removal rate of over 99% by weighing. Dry the eluted elastomer film in a 60°C oven for 2 hours to completely remove any residual moisture. Place the dried elastomer film in a plasma cleaner chamber, evacuate to 10 Pa, introduce oxygen, and set the plasma power to 100W. Treat the upper and lower surfaces of the elastomer for 60 seconds each to complete surface activation. Two pieces of 200-mesh nickel cloth, each 98mm x 8mm, were cut. A thin layer of conductive silver paste was evenly coated on the upper and lower surfaces of the activated elastomer. The conductive layer of nickel cloth was then smoothly attached, and air bubbles were gently pressed to remove them. The mixture was allowed to stand at room temperature for 2 hours to allow the silver paste to cure. A 0.1mm diameter copper wire was soldered to the edge of the nickel cloth as a signal lead. Two PI films, 0.1mm thick and 12mm wide, were cut and placed on the upper and lower nickel cloth surfaces, ensuring that the PI film completely covered the nickel cloth area and extended 1mm beyond the edge of the elastomer. The device was placed in a hot press, with the hot pressing temperature set to 80℃ and the pressure to 0.1MPa, and held for 5 minutes to ensure a tight bond between the PI film and the elastomer, achieving edge sealing. This resulted in a low-porosity porous array flexible electronic skin.
[0039] The electronic skin fabricated in this embodiment underwent comprehensive performance testing: a UTM2503 precision electronic universal testing machine was used to apply gradient pressure loads, and an Agilent E4980A precision LCR meter was used to collect capacitance signals. The test frequency was set to 1kHz, and the test voltage was 1V. The test results showed that the device can stably sense pressure loads ranging from 2g to 300g, and the sensitivity in the low pressure range (0~10kPa) can reach 0.92kPa. -1 Although slightly lower than Example 1, it is still significantly higher than the solid structure control group; the upper limit of the withstand voltage of the device is increased to 300kPa, and the mechanical load-bearing capacity is better than that of Example 1. In the dynamic response test, the device response time is 0.7s and the recovery time is 1.1s, maintaining good dynamic response characteristics; after 100 consecutive load-unload cycle tests, the capacitance response amplitude decay rate is less than 1.6%, and the cycle stability is slightly better than that of Example 1. When the device is applied to the detection of protrusion defects on the surface of fluoroplastic film, it can clearly identify all defects in the height range of 0.15mm to 1mm. The capacitance change shows a good linear relationship with the defect height, and the linear fitting degree R is high. 2 With a value of 0.982, it is suitable for industrial testing scenarios with large loads and higher requirements for device durability.
[0040] Example 3: This example demonstrates the fabrication of a porous array-type flexible electronic skin with high CCTO doping. The dielectric properties and sensitivity are further optimized by increasing the proportion of high-dielectric filler. The specific fabrication steps are as follows: Step 1, Preparation of CCTO nanofibers. Following a stoichiometric ratio of calcium nitrate, copper acetate, and tetrabutyl titanate of 1:3:4, weigh 0.015 mol of calcium nitrate tetrahydrate, 0.045 mol of copper acetate monohydrate, and 0.06 mol of tetrabutyl titanate, and add them sequentially to a dry conical flask. Add 60 mL of a mixture of glacial acetic acid and anhydrous ethanol (volume ratio 1:3) to the conical flask, and stir at 300 rpm for 30 min on a magnetic stirrer until the solutes are completely dissolved, forming a homogeneous blue-green solution. Add 4.8 g of PVP powder with a molecular weight of 1.3 million to the solution, and continue stirring at 400 rpm for 6 h to obtain a transparent and homogeneous blue electrospinning precursor solution, in which PVP accounts for 8% of the total mass of the precursor solution. The precursor solution was loaded into a 10mL medical syringe, fitted with a 21G stainless steel needle, and placed on the injection pump of an electrospinning device. Spinning parameters were set as follows: injection speed 0.8mL / h, spinning voltage 18kV, and vertical distance between the plate receiver and the needle 15cm. The spinning environment temperature was controlled at 25℃ and relative humidity at 40%. Electrospinning was performed with a high-voltage power supply for 3 hours, and a pale blue precursor nanofiber membrane was collected on a plate receiver wrapped in aluminum foil. The collected precursor nanofibers were removed from the aluminum foil, spread evenly in an alumina crucible, and calcined in a tubular resistance furnace. The calcination program was set as follows: heating from room temperature to 850℃ at a rate of 2℃ / min, holding at 850℃ for 2 hours with dry air circulated throughout. After holding, the furnace was allowed to cool naturally to room temperature. The resulting product was a brownish-red pure-phase CCTO nanofiber. Scanning electron microscopy revealed uniform fiber morphology with no obvious agglomeration or breakage.
[0041] Step 2: Sacrificial template preparation and composite slurry curing. A fused deposition modeling (FDM) 3D printer was used to print a mold using PLA filament. The mold's outer dimensions were 120mm × 20mm × 2mm, and the internal groove dimensions were 100mm × 10mm × 1mm. The layer height was 0.1mm, and the wall thickness was 1.2mm. After printing, the inner groove of the mold was polished to ensure a smooth, burr-free inner wall. Using the same 3D printer, but with PVA filament of 88% hydrolysis (model 1788), a sacrificial layer film was printed. The printing parameters were set as follows: nozzle diameter 0.4mm, layer height 0.02mm, linewidth 0.4mm, printing speed 40mm / s, infill pattern of a square grid, infill rate set to 50%, and number of layers set to 5, corresponding to 50% of the full 10-layer printing thickness. A PVA grid sacrificial layer film with dimensions of 98mm × 8mm × 0.1mm was obtained. Weigh 10g of PDMS matrix (Dow Corning Sylgard 184) and 1g of matching curing agent, place them in a plastic beaker, and magnetically stir at 300r / min for 30min to ensure uniform mixing. Add 0.275g of CCTO nanofibers (PDMS to CCTO mass ratio of 40:1), and continue magnetic stirring for 1h to initially disperse the fibers in the PDMS. Then place the beaker in an ultrasonic cleaner, set the ultrasonic power to 200W, and ultrasonically disperse for 40min under ice-water bath conditions to ensure that the high fiber content is fully dispersed and there are no obvious agglomerates. Finally, place the composite slurry in a vacuum drying oven and degas for 15min under a vacuum of -0.09MPa to completely remove air bubbles from the slurry. Slowly inject the degassed composite slurry into the inner groove of the PLA mold until the slurry surface is flush with the mold groove opening; use tweezers to pick up the PVA sacrificial film and slowly place it horizontally into the slurry, adjusting its position so that the film is in the center of the mold and completely immersed in the slurry; place the mold in a vacuum drying oven again for 5 minutes to degauge and remove any remaining tiny air bubbles under the film; finally, place the mold in a 50°C electric constant temperature oven and cure at a constant temperature for 4.5 hours to ensure complete cross-linking of PDMS under the high filler system, thus obtaining a composite elastomer film.
[0042] Step 3, Post-processing and Device Packaging. Remove the mold from the oven and allow it to cool to room temperature. Use tweezers to completely peel off the composite elastomer film along the mold edge. Immerse the elastomer film completely in a beaker containing 60°C deionized water to dissolve and remove the PVA sacrificial layer. Change the deionized water every 6 hours during immersion, and use ultrasound for 10 minutes each time to promote PVA dissolution. After a total immersion time of 24 hours, remove the elastomer film and confirm a PVA removal rate of over 99% by weighing. Dry the eluted elastomer film in a 60°C oven for 2.5 hours to completely remove residual moisture. Place the dried elastomer film in a plasma cleaner chamber, evacuate to 10 Pa, introduce oxygen, set the plasma power to 100W, and treat the upper and lower surfaces of the elastomer for 60 seconds each to complete surface activation. Two 98mm × 8mm pieces of 200-mesh nickel cloth were cut. A thin layer of conductive silver paste was uniformly coated on the upper and lower surfaces of the activated elastomer. The conductive layer of nickel cloth was then smoothly attached, and air bubbles were gently pressed to remove them. The mixture was left to stand at room temperature for 2.5 hours to allow the silver paste to fully cure. A 0.1mm diameter copper wire was soldered to the edge of the nickel cloth as a signal lead. Two 0.1mm thick and 12mm wide PI films were cut and placed on the upper and lower nickel cloth surfaces, ensuring that the PI films completely covered the nickel cloth area and extended 1mm beyond the edge of the elastomer. The device was placed in a hot press, and the hot pressing temperature was set to 80℃, the pressure to 0.1MPa, and the pressure was held for 5 minutes to complete the sealing and encapsulation. Finally, a porous array flexible electronic skin with high CCTO doping was obtained.
[0043] The electronic skin prepared in this embodiment was subjected to performance testing: a test platform was built using a precision electronic universal testing machine and an LCR meter, with a test frequency of 1kHz and a test voltage of 1V. The test results showed that the initial capacitance of the device was increased by 18% compared to Example 1, and the sensitivity in the low-pressure range (0~10kPa) reached 1.41kPa. -1 The sensitivity is further improved compared to Example 1; the device can stably sense pressure loads within the range of 0.8g to 180g, with a lower minimum detection limit and stronger ability to sense minute pressures. In dynamic response testing, the device's response time is 0.6s and recovery time is 1.1s, maintaining good dynamic response speed; after 100 consecutive load-unload cycle tests, the capacitance response amplitude decay rate is 2.3%, still meeting the requirements for long-term industrial use. When applied to the detection of minute defects on the surface of fluoroplastic films, the device can clearly identify protruding defects within the height range of 0.08mm to 1mm, with superior detection capability for ultra-small defects, making it suitable for high-precision quality control scenarios.
[0044] Comparative Example 1 (Solid Structure Control Group): This comparative example prepared a solid CCTO / PDMS flexible electronic skin without a porous array structure. Except for the absence of a PVA sacrificial layer film, the other raw material ratios, preparation processes, and packaging methods were exactly the same as in Example 1.
[0045] Performance test results show that the sensitivity of this control device in the 0~10kPa range is only 0.14kPa. -1 The pressure is much lower than the 1.25 kPa in Example 1. -1 In fluoroplastic film defect detection, only protruding defects with a height of 0.5 mm or more can be identified, with no significant response to minute defects smaller than 0.5 mm, failing to meet the requirements for high-precision detection. This comparative example verifies the crucial role of porous array structures in improving device sensitivity and enabling the detection of minute defects.
[0046] Comparative Example 2 (CCTO Particle Control Group): In this comparative example, zero-dimensional CCTO nanoparticles were used to replace the CCTO nanofibers in Example 1 as fillers. The CCTO doping mass ratio, porous structure parameters, and other preparation processes were exactly the same as in Example 1.
[0047] Performance test results show that, due to the tendency of nanoparticles to aggregate, the capacitance response uniformity of this control device is poor, with sensitivity deviations exceeding 15% in different regions; the average sensitivity in the 0–10 kPa range is 0.78 kPa. -1 The composite material exhibits lower modulus than the nanofiber-filled system in Example 1; however, it also has a higher modulus but lower flexibility, and cracking occurs at the electrode interface after 100 bends. This comparative example verifies the significant advantages of one-dimensional CCTO nanofibers in terms of dispersibility, performance uniformity, and flexibility retention.
[0048] Comparative Example 3 (Pure PDMS Control Group): This comparative example prepared a pure PDMS-based porous array electronic skin without any CCTO filler. The remaining porous structure parameters, preparation process and packaging method were exactly the same as those in Example 1.
[0049] Performance test results show that the control example device has a low initial capacitance value and a sensitivity of only 0.31 kPa in the 0~10 kPa range. -1 The results were significantly lower than in Example 1; moreover, the linearity of the capacitance response was poor, and the signal was prone to saturation in the high-voltage range. This comparative example verifies the core role of high-dielectric CCTO filler in improving the capacitance response and sensitivity of the device, and demonstrates the synergistic effect of the filler and porous structure in this invention.
[0050] By comparing the examples and the control examples, it is clear that the present invention achieves a significant improvement in the sensitivity of flexible electronic skin through the synergistic effect of CCTO nanofiber doping and the construction of a porous array structure using 3D printed sacrificial templates. At the same time, it has excellent stability and conformal bonding ability, which can effectively solve the technical pain point of detecting minute defects in industrial fluoroplastic films and has significant technological progress and industrial application value.
[0051] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of protection claimed by the present invention. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for fabricating porous array flexible electronic skin based on the sacrificial template method, characterized in that, Includes the following steps: Step 1: Calcium nitrate, copper acetate, and tetrabutyl titanate are mixed in a molar ratio of 1:3:
4. Polyvinylpyrrolidone is added and dissolved in a mixed solution of acetic acid and ethanol. After stirring for 6 hours, a blue transparent solution is formed. Light blue precursor nanofibers are obtained by electrospinning. The nanofibers are collected and placed in a tube furnace for heat treatment to obtain CCTO nanofibers. Step 2: Prepare a PLA mold with an inner groove size of 100mm×10mm×1mm by 3D printing, and then prepare a PVA sacrificial layer film by 3D printing. Mix PDMS, curing agent and CCTO nanofibers thoroughly to obtain a composite slurry and pour it into the mold. Place a PVA sacrificial layer film of appropriate size into the mold, remove air bubbles and cure and dry at 50℃ to obtain a composite elastomer film. Step 3: Remove the composite elastomer membrane and place it in deionized water. After removing the PVA sacrificial layer film, attach a nickel cloth conductive layer to the upper and lower surfaces of the composite elastomer membrane and lead out wires. Then, encapsulate and protect it with a polyimide film to obtain a porous array flexible electronic skin based on the sacrificial template method.
2. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: In step 1, the temperature of the tubular furnace heat treatment is 850℃, the holding time is 2h, the heating rate is 2℃ / min, and the heat treatment atmosphere is air.
3. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: In step 1, the molecular weight of polyvinylpyrrolidone is 1.3 million, and the amount added is 8% of the total mass of the precursor solution; the volume ratio of acetic acid to ethanol is 1:3; the process parameters of electrospinning are: spinning voltage 18kV, receiving distance 15cm, injection speed 0.8mL / h, needle specification 21G, ambient temperature 25℃, and relative humidity 40%.
4. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: In step 2, the PVA sacrificial layer film is prepared using a sparse printing process with a fill rate of 50%, meaning the ratio of the area covered by the printed lines to the total area of the film is 50%, the number of printed layers is 50% of the number of full-layer printed layers, and the filling pattern is a square grid array.
5. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: In step 2, the mass ratio of PDMS to curing agent is 10:1, and the mass ratio of PDMS to CCTO nanofibers is 50:
1. The mixing process of the composite slurry is as follows: first, PDMS and curing agent are magnetically stirred for 30 minutes, CCTO nanofibers are added and magnetic stirring is continued for 1 hour, then ultrasonically dispersed for 30 minutes, and then vacuum degassing is performed for 10 minutes.
6. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: Before attaching the nickel cloth conductive layer in step 3, the upper and lower surfaces of the composite elastomer film need to be treated with oxygen plasma in advance. The treatment power is 100W, the treatment time is 60s, and the vacuum degree is 10Pa.
7. The method for fabricating porous array flexible electronic skin based on the sacrificial template method according to claim 1, characterized in that: In step 3, the polyimide film has a thickness of 0.1 mm and a width of 12 mm. During encapsulation, the polyimide film completely covers the nickel cloth conductive layer and extends 1 mm beyond the edge of the composite elastomer film. Sealing is achieved by hot pressing.
8. A porous array flexible electronic skin based on the sacrificial template method, characterized in that, The electronic skin is prepared by any one of the preparation methods described in claims 1 to 7. The electronic skin includes an upper polyimide encapsulation layer, an upper nickel cloth conductive layer, a porous array CCTO / PDMS composite dielectric layer, a lower nickel cloth conductive layer, and a lower polyimide encapsulation layer, which are stacked sequentially from top to bottom. The porous array CCTO / PDMS composite dielectric layer has a regularly distributed array of through-hole structures inside.